2015
DOI: 10.1021/acsnano.5b00641
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of ATP-Responsive Drug Release Using Mesoporous-Silica-Coated Multicolor Upconversion Nanoparticles

Abstract: Stimuli-responsive drug delivery vehicles have garnered immense interest in recent years due to unparalleled progress made in material science and nanomedicine. However, the development of stimuli-responsive devices with integrated real-time monitoring capabilities is still in its nascent stage because of the limitations of imaging modalities. In this paper, we describe the development of a polypeptide-wrapped mesoporous-silica-coated multicolor upconversion nanoparticle (UCNP@MSN) as an adenosine triphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(113 citation statements)
references
References 70 publications
(133 reference statements)
0
110
0
Order By: Relevance
“…Owning to the upregulated ATP level, many researchers have tried to design ATP-responsive drug-release systems that can specifically recognize ATP as well as the competitive binding with ATP aptamer. [122][123][124][125][126] Lai et al 122 developed an ATP-responsive DDS for realtime monitoring of drug release. As shown in Figure 11, the mesoporous-silica-coated up-conversion nanoparticle (UCNP@MSN) was wrapped with a compact branched polypeptide, poly(Asp-Lys)-b-Asp, and then functionalized with zinc-dipicolylamine analogue (TDPA-Zn 2+ ) on its exterior surface.…”
Section: Msns For Stimuli-responsive Controlled Drug Deliverymentioning
confidence: 99%
“…Owning to the upregulated ATP level, many researchers have tried to design ATP-responsive drug-release systems that can specifically recognize ATP as well as the competitive binding with ATP aptamer. [122][123][124][125][126] Lai et al 122 developed an ATP-responsive DDS for realtime monitoring of drug release. As shown in Figure 11, the mesoporous-silica-coated up-conversion nanoparticle (UCNP@MSN) was wrapped with a compact branched polypeptide, poly(Asp-Lys)-b-Asp, and then functionalized with zinc-dipicolylamine analogue (TDPA-Zn 2+ ) on its exterior surface.…”
Section: Msns For Stimuli-responsive Controlled Drug Deliverymentioning
confidence: 99%
“…5,9,20,23 Briefly, 2.4 g of CTAB was dissolved in deionized water (800 mL) with vigorous stirring at 80°C. Then 3.6 mL of NaOH (2 mol/L) was dissolved into the solution and stirred vigorously for 2 continual hours.…”
Section: Preparation Of Dox@ha-pl-msns Synthesis Of Msnsmentioning
confidence: 99%
“…HeLa cells were seeded in a 12-well plate (5×10 4 cells per well) and incubated for 8 h. After washing twice with PBS, the cells were incubated with FITC-labeled MSNs, PL-MSNs, or HA-PL-MSNs in 2 mL of the serum-free DMEM medium for 5 h. The cells were subsequently washed three times with 4°C PBS to remove the remaining nanoparticles and dead cells, and the cells were investigated under a confocal laser scanning microscope (CLSM, Leica [Wetzlar, Germany], TCS SP8). 3,23 For competitive inhibition studies, the medium was replaced with 2 mL serum-free culture medium containing HA polymer (10 mg/mL) and then FITC-labeled HA-PLMSNs (20 mg/mL) in HeLa cells, 28,29 followed by the same treatment as described earlier. In order to further confirm competitive inhibition studies of HA to CD44, NIH3T3 cells 5,6,19 were cultured in the same way.…”
mentioning
confidence: 99%
“…They found that the tumor growth inhibition effect of this platform was much higher than that of chemotherapy or photothermal therapy alone. More recently, Lai et al monitored the real-time ATP-stimulated drug release with mesoporous-silica coated multicolor UCPs, as shown in Figure 5 [83]. The mesoporous-silica coated UCPs were functionalized with zinc-dipicolyamine analog on their surface and loaded with polypeptide wrapped chemotherapeutics in mesopores.…”
Section: Inorganic Nanoparticle-based Cancer Therapymentioning
confidence: 99%